Development Strategy of Shrimp Shell Waste Processing Bussiness (Study in Banyuwangi and Situbondo Regency) - Herna Octivia Damayanti; Ratna Dewi Judhaswati; Darmawan Soecahyo (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2019)
The high production and export in processed form of shrimp produces side product in the form of shrimp shell waste. The problem faced was so far, the shrimp shell waste has not been processed into products that have high selling value, namely in the form of organic fertilizer and liquid fertilizer containing chitin. The research objective was to formulate strategy in the effort to develop shrimp shell waste processing business. This research is a descriptive with quantitative and qualitative approach and was held in May-October 2018. Locations in Situbondo and Banyuwangi Regencies. Respondents came from 2 districts, namely Situbondo and Banyuwangi Regency. Data collection techniques with FGD and filling out questionnaires. Data analysis using SWOT analysis and QSPM. Research results are the order of priority strategies: (1) protection and commitment to business development, (2) increasing business capacity and quality of human resources of business people, (3) business promotion in coastal areas that are potential in the market to investors, (4) efforts to open market access for shrimp shell waste processing products, (5) dissemination of the existence of shrimp shell waste processing business to the community, (6) synergy between joint unit group and the government in the development of processing businesses.